Molecular Diagnosis of Brucella species in Baghdad (Baghdad Science Journal, 2013)
Brucellosis is possess a significant public health problem in Baghdad. In this study, we investigated the potential role of the PCR assay in detection of Brucella species, from patients suspect to have brucellosis, using blood samples in both human and animal.To establish a PCR technique for diagnosis of active brucellosis in our samples, DNA extraction was carried out using a commercial kit, and a laboratory extraction procedure. PCR amplification was done using 1 set of primers: B4/B5 for Brucella species. Extraction of Brucella DNA using the commercial kit was successful. The laboratory extraction was successful and more economic. A total of 178 peripheral blood specimens were collected from patients with high suspected brucellosis, and 15 samples from animals. When PCR technique was applied to blood samples, 13 cases for patients blood and 9 cases for animals blood, were positive for Brucella species.